2008
DOI: 10.1007/s12369-008-0002-2
|View full text |Cite
|
Sign up to set email alerts
|

Where Robots and Virtual Agents Meet

Abstract: Traditionally, social interaction research has concentrated on either fully virtually embodied agents (e.g. embodied conversational agents) or fully physically embodied agents (e.g. robots). For some time, however, both areas have started augmenting their agents' capabilities for social interaction using ubiquitous and intelligent environments.We are placing different agent systems for social interaction along Milgram's Reality-Virtuality Continuumaccording to the degree they are embodied in a physical, virtua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…Moreover, similar to Nass and his colleagues, research has found that many of the rules that subjects apply to human-human interaction, are also brought over to humanagent interaction (Pertaub et al 2002). This is why research has hypothesised that despite technical differences between dealing with robotic and virtual domains, today a many issues behind the construction of successful social agents cross the boundaries of virtual agent species as well (Holz et al 2009). Therefore, it is predicted:…”
Section: Technology-oriented Differencesmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, similar to Nass and his colleagues, research has found that many of the rules that subjects apply to human-human interaction, are also brought over to humanagent interaction (Pertaub et al 2002). This is why research has hypothesised that despite technical differences between dealing with robotic and virtual domains, today a many issues behind the construction of successful social agents cross the boundaries of virtual agent species as well (Holz et al 2009). Therefore, it is predicted:…”
Section: Technology-oriented Differencesmentioning
confidence: 91%
“…On the other hand, in today's digital society, where a growing amount of human activities relies on the incorporation of virtual characters into virtual and augmented reality environments (Holz et al 2009), ever more companies and organisations are using avatars to increase consumer interaction, support students in learning environments (Chittaro et al 2003) and engage users with more personalised services (Belisle and Bodur 2010). In fact, there is a growing body of research on how the use of virtual selfrepresentations affects many factors both within virtual environments and outside of them (Ratan and Hasler 2010).…”
Section: Technology-oriented Differencesmentioning
confidence: 99%
“…Much of the research in this area is performed under the title of affective computing, a domain which explores how interaction with an interface influences the emotional state, feelings, and satisfaction of the person [61], whether through deliberate design (e.g., [5]) or as an incidental artifact of interaction (e.g., [45,61]). This area of research also includes the evaluation of interaction with virtual agents, work of particular interest to HRI [40] as virtual agents can also elicit agency and social presence (although not physical), and an area of potential influence for the evaluation of social interaction with robots. Given the socially situated and activeagency nature of interaction with robots, we feel that this body of work is particularly relevant.…”
Section: Emotion and Affective Computingmentioning
confidence: 99%
“…For cognitive neuroscience and psychology, it is concerned with the question of how the brain represents the body (Berlucchi & Aglioti, 1997;Graziano & Botvinick, 2002) and how this representation is altered under certain neurological conditions (Lenggenhager, Smith, & Blanke, 2006;Metzinger, 2009). In contrast, in robotics, the concept is employed to distinguish ways through which artificial forms of intelligence are represented contrasting those virtual agents and robots that have a real physical representation compared to those that do not (Foster, 2007;Holz, Dragone, & O'Hare, 2009;Wainer, Feil-Seifer, Shell, & Mataric, 2006). Embodiment has been also discussed in relation to presence in virtual environments (Biocca, 1997), especially as there is evidence to suggest that a virtual body in the context of a head-mounted display based virtual reality is a critical contributor to the sense of being in the virtual location (Slater, Spanlang, & Corominas, 2010).…”
Section: Introductionmentioning
confidence: 99%